Comparative efficacy and safety of systemic antifungal agents for candidemia: a systematic review with network meta-analysis and multicriteria acceptability analyses - Domingos, Eric L. (2022)
Aim: Invasive candidiasis is the main fungal infection in patients attending health services and is associated with high mortality rates and prolonged hospital stay. We aimed to comparatively evaluate the efficacy and safety of antifungal agents for treating candidemia. Methods: A systematic review with network meta-analysis (NMA), the surface under the cumulative ranking analysis (SUCRA), and stochastic multicriteria acceptability analyses (SMAA) were performed (PROSPERO-CRD42020149264). Searches were conducted in PubMed and Scopus (Nov-2021). Randomised controlled trials evaluating the effect of oral antifungals (any dose or regimen) on mycological cure, discontinuation rates, and adverse events were included. Results: Overall, 13 trials (n=3,632) were analysed. No significant differences among therapies were found for the efficacy outcomes; however, caspofungin (50-150 mg), rezafungin (200-400mg), and micafungin (100-150 mg) were considered the most promising therapies, leading to higher rates of both clinical and mycological responses (SUCRA overall response over 60%). Fluconazole (400 mg) was rated as the last option for overall response (17%). Rezafungin (200-400mg) and micafungin (100 mg) were associated with lower discontinuation rates (<40%); conventional amphotericin B (0.6-0.7mg/kg) was more likely to be discontinued (OR 0.08 [95% CrI 0.00-0.95] vs. caspofungin 150 mg) and may impair liver function (87%). Conclusion: Echinocandins should be listed as first-line treatments for invasive candidiasis following a priority order of caspofungin and micafungin. Rezafungin, an under-development echinocandin, represents a potential option that should be further investigated. Azoles and liposomal amphotericin B can be used as second-line treatments in cases of fungal resistance or hypersensitivity.